1985
DOI: 10.1038/bjc.1985.51
|View full text |Cite
|
Sign up to set email alerts
|

Goblet cell changes during intestinal adaptation to azoxymethane and enteric bypass in the rat

Abstract: Summary Numbers of intestinal goblet cells containing specific acid mucins were determined in male Sprague-Dawley rats receiving azoxymethane (total dose 90mg kg-1) with or without jejunoileal bypass (JIB). Controls During the latent period of experimental colonic carcinogenesis, changes occur in the relative proportions of specific acid mucins elaborated by the goblet (mucous) cells. Twenty weeks after exposure to azoxymethane or dimethylhydrazine, rats show a substantial increase in the number of goblet ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Brown et al [22] have suggested that these changes may re flect a maturation of the goblet cell as it migrates up the villi. While several studies have found similar staining results [17,19,20], Subbuswamy [16] observed that goblet cells lining the villi in jejunum and ileum stained almost entirely PAS+.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Brown et al [22] have suggested that these changes may re flect a maturation of the goblet cell as it migrates up the villi. While several studies have found similar staining results [17,19,20], Subbuswamy [16] observed that goblet cells lining the villi in jejunum and ileum stained almost entirely PAS+.…”
Section: Discussionmentioning
confidence: 63%
“…Differentiated goblet cells migrate with the columnar cells up the villi, releasing a mucous layer over the epithelial surface of the intestinal tract [5][6][7][8]. This mucous layer is important for the pro tection of the underlying mucosa by exclud ing irritants such as antigens, toxins, and gastrointestinal enzymes [9][10][11][12], Other func tions that have been attributed to the mu cous layer are lubrication of the surface for the facilitation of luminal content passage [12,13], removal of parasites [14], and maintenance of a fairly constant pH at the unstirred surface layer [12,15], There have been several histochemical studies of intestinal epithelial mucosubstances in many species under normal con ditions [16][17][18], and in altered states [19,20]. Studies in the pig have been under taken by Rahko and Saloniemi [21] and Brown et al [22], The above studies, of a qualitative nature, have been limited to a few specific areas in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…The proliferative effect was 218% greater than that seen in wild-type mice, resulting in an increase in the thickness of the colonic mucosa along with colonic goblet cell hyperplasia of MTI/G-GLY mice when compared with wild-type mice. Goblet cell hyperplasia has been reported in other rodent models in which colonic proliferation has been induced (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…While small intestinal goblet cell hyperplasia results from azoxymethane administration [ 68 ] and massive small intestinal resection [ 69 ], pathogenic bacteria and parasites are the only natural causes of intestinal goblet cell hyperplasia [ 70 , 71 ], including the protozoan parasite Giardia lamblia/intestinalis [ 72 ], the helminthes Trichinella spiralis [ 73 ] and Nippostrongylis brasiliensis [ 74 , 75 ], the bacteria Yersinia enterocolitica [ 76 ] and various Shigella species [ 77 ].…”
Section: Introductionmentioning
confidence: 99%